2021
DOI: 10.7759/cureus.17621
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Association of Maternal Nutritional Status With Neonatal Birth Weight in Term Pregnancies: A Cross-Sectional Study With Unexpected Outcomes

Abstract: IntroductionBirth weight is described as the primary determinant of the chances of survival among newborns. Low birth weight (LBW) is considered to be a major public health issue, especially among developing countries where poor maternal nutritional status is identified as a cause of both long and short-term adverse consequences. In developing countries, the majority of the LBW infants are born at term but are affected by intrauterine growth restriction, which might have begun early in the pregnancy period. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…Similarly, several studies have demonstrated a significant relationship between the two variables, corroborating the results of this study (Rani et al 2017, Puspitaningrum 2018, Siyoum & Melese 2019. In contrast, a study conducted by Sangi et al (2021) revealed that there was no statistically significant relationship between maternal MUAC and infant birth weight (p=0.145). However, there was a moderate correlation (R=0.117) observed between the variables.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, several studies have demonstrated a significant relationship between the two variables, corroborating the results of this study (Rani et al 2017, Puspitaningrum 2018, Siyoum & Melese 2019. In contrast, a study conducted by Sangi et al (2021) revealed that there was no statistically significant relationship between maternal MUAC and infant birth weight (p=0.145). However, there was a moderate correlation (R=0.117) observed between the variables.…”
Section: Discussionsupporting
confidence: 90%
“…They gave birth to babies with a birth weight within the normal range instead. In a recent study conducted by Sangi et al (2021), it was found that only 26.3% of infants born to mothers with nutritional problems had a low birth weight. However, there is an opposing notion suggesting a correlation between maternal MUAC and infant birth weight.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Maternal factors related to neonatal death were caused by underlying diseases contributing to pregnancy complications (Ndayisenga, 2016). Mothers with chronic diseases such as kidney disease, hypertension and diabetes have high-risk morbidity and mortality during labor (Grandi et al, 2015;Huang et al, 2022;Nuccio & Chonchol, 2016). The most life-threatening experience is ante or post-postpartum hemorrhage, which is significantly related to neonatal or maternal death (Hough et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The gain of excessive gestational weight and the presence of metabolic comorbidities is one of the maternal factors associated with the birth of LGA babies, while insufficient gestational weight gain is associated with the birth of SGA babies 9,10 . Birth weight is described as the main determinant of the chances of newborns' survival, and has been significantly associated with various factors, such as the mother's level of education, the number of prenatal appointments, ethnicity/race, and maternal weight during pregnancy 11,12 , including food deserts 13 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review)…”
Section: Introductionmentioning
confidence: 99%